HIV test-and-treat policy improves clinical outcomes in Zambian adults from Southern Province: a multicenter retrospective cohort study - Hamooya, Benson M.; Mutembo, Simon; Muyunda, Brian; Mweebo, Keith; Kancheya, Nzali; Sikazwe, Lyapa; Sakala, Morgan; Mvula, Johanzi; Kunda, Salazeh; Kabesha, Shem; Cheelo, Chilala; Fwemba, Isaac; et al. (Frontiers in Public Health, 2023)
Background Globally, most countries have implemented a test-and-treat policy to reduce morbidity and mortality associated with HIV infection. However, the impact of this strategy has not been critically appraised in many settings, including Zambia. We evaluated the retention and clinical outcomes of adults enrolled in antiretroviral therapy (ART) and assessed the impact of the test-and-treat policy. Methods We conducted a retrospective cohort study among 6,640 individuals who initiated ART between January 1, 2014 and July 31, 2016 [before test-and-treat cohort (BTT), n = 2,991] and between August 1, 2016 and October 1, 2020 [after test-and-treat cohort (ATT), n = 3,649] in 12 districts of the Southern province. To assess factors associated with retention, we used logistic regression (xtlogit model). Results The median age [interquartile range (IQR)] was 34.8 years (28.0, 42.1), and 60.2% (n = 3,995) were women. The overall retention was 83.4% [95% confidence interval (CI) 82.6, 84.4], and it was significantly higher among the ATT cohort, 90.6 vs. 74.8%, p < 0.001. The reasons for attrition were higher in the BTT compared to the ATT cohorts: stopped treatment (0.3 vs. 0.1%), transferred out (9.3 vs. 3.2%), lost to follow-up (13.5 vs. 5.9%), and death (1.4 vs. 0.2%). Retention in care was significantly associated with the ATT cohort, increasing age and baseline body mass index (BMI), rural residence, and WHO stage 2, while non-retention was associated with never being married, divorced, and being in WHO stage 3. Conclusion The retention rate and attrition factors improved in the ATT compared to the BTT cohorts. Drivers of retention were test-and-treat policy, older age, high BMI, rural residence, marital status, and WHO stage 1. Therefore, there is need for interventions targeting young people, urban residents, non-married people, and those in the symptomatic WHO stages and with low BMI. Our findings highlight improved ART retention after the implementation of the test-and-treat policy.